Northern outpost for Mediterranean scaldfish: encounters from Norwegian coastal and oceanic waters, NE Atlantic Ocean - Ringvold, H.; Vesterinen, Eero J.; Monto, E.; van der Meeren, T. (SPRINGER HEIDELBERG, 2026)
The Mediterranean scaldfish Arnoglossus laterna (Walbaum, 1792) is distributed in the eastern Atlantic, from Angola, via the Mediterranean and Black Sea, north to Norway. While this species is used for human consumption in southern parts, it is considered a non-commercial flatfish in the North Sea. It is rarely reported from its northern outpost, Norwegian waters. Knowledge on biology, habitat, location of spawning areas, larval distribution, and juvenile nursery grounds in the North Sea is limited. We include observations of A. laterna from 1876 to 2023 from a pool of both published and unpublished sources, along the Norwegian coast. Frequency distributions from Institute of Marine Research (IMR) data of adults show the highest encounters with specimens collected between 30 and 40 m depth, weighing 6-9 g and measuring between 6 and 11 cm in total length. Eggs and larvae were observed in both offshore and inshore waters between April and November. One larva recorded in Vestland County (Haganes, Bergen) was found as shallow as 20 cm depth swimming close to the ctenophore Mnemiopsis leidyi A. Agassiz, 1865, likely hiding from predators. Both blue and yellow bioluminescent spots on the larva were observed, visible as two bands on the dorsal- and anal fins. This larva specimen was preserved for barcoding (using sequences COI, ITS1, ITS2 and 16 s), confirming the morphological identification. The largest specimen obtained in this study (from Arendal) measured 26.5 cm in length, and is probably the largest individual ever recorded, indicating good conditions for growth.